2022
DOI: 10.1097/ju.0000000000002342
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Nutritional Risk Index Predicts Postoperative Outcomes in Bladder Cancer: A Propensity Score-Matched Analysis

Abstract: Purpose: The Geriatric Nutritional Risk Index (GNRI) is a simple screening tool to predict nutrition-related risk of morbidity and mortality in older patients. We assessed whether preoperative GNRI was associated with 30-day complications after radical cystectomy (RC). Materials and Methods: Using the American College of Surgeons National Surgical Quality Improvement Program database, we identified patients 65 years or older who underwent RC for the treatment of bladder cancer between 2007 and 2019. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…The AAPR and NRI are also based on albumin, which has been verified as a prognostic factor for many cancers. 21,[38][39][40][41] In our study, low NRI and low AAPR were significantly related to poor OS. Moreover, as observed in previous studies, performance status, LDH, and age were significantly related to survival outcomes in our patients with MM.…”
Section: Discussionsupporting
confidence: 53%
“…The AAPR and NRI are also based on albumin, which has been verified as a prognostic factor for many cancers. 21,[38][39][40][41] In our study, low NRI and low AAPR were significantly related to poor OS. Moreover, as observed in previous studies, performance status, LDH, and age were significantly related to survival outcomes in our patients with MM.…”
Section: Discussionsupporting
confidence: 53%
“…Riveros et al . found that in bladder cancer patients receiving radical cystectomy, GNRI independently predicts mortality, blood transfusion, pneumonia, extended length of stay and non-home discharge 16 . Additional to survival and perioperative complications outcome, they also suggest that low GNRI was associated with extended length of hospital stay and nonhome discharge.…”
Section: Discussionmentioning
confidence: 95%
“…In a large-scale retrospective study, Kang et al found that low values of GNRI are associated with aggressive pathologic characteristics and poor survival in patients with renal clear cell carcinoma who have nephrectomy 17 . Riveros et al found that in bladder cancer patients receiving radical cystectomy, GNRI independently predicts mortality, blood transfusion, pneumonia, extended length of stay and non-home discharge 16 . Additional to survival and perioperative complications outcome, they also suggest that low GNRI was associated with extended length of hospital stay and nonhome discharge.…”
Section: Discussionmentioning
confidence: 99%
“…PEM has been associated with a number of health outcomes, disease states, and illnesses [16,17]. The Geriatric Nutritional Risk Index (GNRI) is a simple screening tool to investigate nutrition-related dose-response association with morbidity and mortality of diseases [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%